2001
DOI: 10.1002/1521-2254(2000)9999:9999<::aid-jgm152>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Optimised helper virus-free production of high-quality adeno-associated virus vectors

Abstract: This work demonstrates the possibility of producing purified high-quality rAAV free of helper virus. The procedure described in this paper is easily adaptable for large-scale production of clinical rAAV vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…46 In addition to a nuclease, some purification methods require detergents and protease treatment. 20,36,[46][47][48][49][50] Some of these additives are hard to eliminate and therefore cannot be used for commercial manufacturing. In contrast to Ad, the relative stability of the AAV particle to heat, mild proteolytic digestion and nonionic detergents allows it to withstand robust purification procedures, thus facilitating scaled-up production.…”
Section: Virus Harvesting and Initial Purification Stepsmentioning
confidence: 99%
“…46 In addition to a nuclease, some purification methods require detergents and protease treatment. 20,36,[46][47][48][49][50] Some of these additives are hard to eliminate and therefore cannot be used for commercial manufacturing. In contrast to Ad, the relative stability of the AAV particle to heat, mild proteolytic digestion and nonionic detergents allows it to withstand robust purification procedures, thus facilitating scaled-up production.…”
Section: Virus Harvesting and Initial Purification Stepsmentioning
confidence: 99%
“…Adeno-associated viral vectors, for example, can transduce muscle with high efficiency. [2][3][4][5] However, therapeutic application would require a number of improvements including efficient and reliable procedures for the manufacture of viral vectors, free of helper virus 6 and reduction in immunogenicity. The high efficiency of random integration of most viral vectors into host genome poses a potential risk of vector-related insertional mutagenesis and interference with expression of cellular genes.…”
Section: Introductionmentioning
confidence: 99%
“…12 Ultrasound is particularly effective for gene delivery when applied in combination with the use of microbubbles, cationic polymers or lipids. [3][4][5][6][7][8][9][10][11][12][13][14][15] Anwer et al 15 reported that application of ultrasound to skin tumours before or after the injection of lipoplexes resulted in a significant increase in gene transfer specifically to the tumour. 15 The magnitude of increased expression ranged from 3-4 to 270-fold.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] While the majority of gene therapy experiments and clinical trials currently use viral delivery systems, [12][13][14] several aspects need to be improved to achieve therapeutic benefit in patients. These include better efficiency and reliability of procedures for the manufacture of virus, freedom from helper virus contamination, 15 avoidance of immunogenicity of the viral particle itself, and ways of overcoming the limitation of transgene size. [16][17][18] In several of these respects, non-viral delivery systems have clear advantages over viral delivery systems.…”
Section: Introductionmentioning
confidence: 99%